2006
DOI: 10.1111/j.1365-2958.2006.05110.x
|View full text |Cite
|
Sign up to set email alerts
|

Influences on gene expression in vivo by a Shine–Dalgarno sequence

Abstract: SummaryThe Shine-Dalgarno (SD + : 5 ¢ -AAGGAGG-3 ¢ ) sequence anchors the mRNA by base pairing to the 16S rRNA in the small ribosomal subunit during translation initiation. We have here compared how an SD + sequence influences gene expression, if located upstream or downstream of an initiation codon. The positive effect of an upstream SD + is confirmed. A downstream SD + gives decreased gene expression. This effect is also valid for appropriately modified natural Escherichia coli genes. If an SD + is placed be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 76 publications
(108 reference statements)
2
26
0
1
Order By: Relevance
“…Low protein expression using pBAD24 vector has been reported (Golich et al 2006;Oku et al 2004;Nelson et al 2006;Marolda et al 2004;Jin et al 2006) but no reason for this has been given. This prompted us to look into the reasons for such an experimental finding.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Low protein expression using pBAD24 vector has been reported (Golich et al 2006;Oku et al 2004;Nelson et al 2006;Marolda et al 2004;Jin et al 2006) but no reason for this has been given. This prompted us to look into the reasons for such an experimental finding.…”
Section: Discussionmentioning
confidence: 91%
“…Jacob et al (1987) and Jin et al (2006) report that a single base change in the SD sequence causes a dramatic change in the synthesis of many proteins. We, therefore, modified the existing SD sequence of the pBAD24T7g10 vector to create pBAD24M where the optimized SD sequence from the T7 system was incorporated.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Jin et al (16) reported that when an SD motif is located between two potential start codons, initiation occurs predominantly at the second start site; the first start site is utilized when the distance between this site and the downstream SD motif is increased and/or when the second start site is weakened. In that study, the authors found that the SD motif is systematically avoided in the early coding region of natural genes in Escherichia coli, possibly reflecting a strong evolutionary constraint for codon usage (16).…”
mentioning
confidence: 99%
“…Jin et al (16) reported that when an SD motif is located between two potential start codons, initiation occurs predominantly at the second start site; the first start site is utilized when the distance between this site and the downstream SD motif is increased and/or when the second start site is weakened. In that study, the authors found that the SD motif is systematically avoided in the early coding region of natural genes in Escherichia coli, possibly reflecting a strong evolutionary constraint for codon usage (16). In rare cases, bacterial gene transcripts contain an internal start codon that is preceded by a strong SD motif (e.g., GGAGG); thus, alternative translation initiation leads to the generation of two isoforms of the protein, as evidenced by the heat shock proteins ClpB (17) and ClpA (18), initiation factor 2 (IF2) (19), hemolysin (20), and lycopene cyclase (21).…”
mentioning
confidence: 99%